Compositional and Optical Gradient in Films of PbZrxTi1-xO3 (PZT) Family - Aulika, Ilze; Dejneka, Alexandr; Mergan, Silvana; Crepaldi, Marco; Jastrabik, Lubomir; Zhang, Qi; Benčan, Andreja; Kosec, Maria; Zauls, Vismants (IntechOpen, 2011)
None